2017
DOI: 10.1093/mnras/stx3204
|View full text |Cite
|
Sign up to set email alerts
|

The age–velocity dispersion relation of the Galactic discs from LAMOST–Gaia data

Abstract: We present the age-velocity dispersion relation (AVR) in three dimensions in the solar neighbourhood using 3,564 commonly observed sub-giant/red-giant branch stars selected from LAMOST, which gives the age and radial velocity, and Gaia, which measures the distance and proper motion. The stars are separated into metal-poor ([Fe/H] < −0.2 dex and metal-rich ([Fe/H] > −0.2 dex) groups, so that the metal-rich stars are mostly α-poor, while the metalpoor group are mostly contributed by α-enhanced stars. Thus, the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
90
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 67 publications
(81 reference statements)
18
90
2
Order By: Relevance
“…Our result that σ z /σ R increases with age in the low [α/Fe] disc is clearly in-line with this picture of heating by non-stationary processes. A similar scenario was proposed also by Yu & Liu (2018), whose results on the velocity ellipsoid shape are consistent with those presented here. Jenkins & Binney (1990) showed that increasing the importance of spirals over GMCs reduced σ z /σ R , such that models that have the most dominant spiral arm perturbations have the lowest σ z /σ R .…”
Section: Velocity Ellipsoid Shapesupporting
confidence: 93%
See 1 more Smart Citation
“…Our result that σ z /σ R increases with age in the low [α/Fe] disc is clearly in-line with this picture of heating by non-stationary processes. A similar scenario was proposed also by Yu & Liu (2018), whose results on the velocity ellipsoid shape are consistent with those presented here. Jenkins & Binney (1990) showed that increasing the importance of spirals over GMCs reduced σ z /σ R , such that models that have the most dominant spiral arm perturbations have the lowest σ z /σ R .…”
Section: Velocity Ellipsoid Shapesupporting
confidence: 93%
“…Combining all the MCMC samples for these bins, we find σ z /σ R = 0.64 ± −0.04. This value is in rough agreement with the measurements of σ R /σ z in LAMOST-TGAS stars by Yu & Liu (2018).…”
Section: The Shape Of the Velocity Ellipsoid As A Function Of Agesupporting
confidence: 90%
“…Since the older stars have been experiencing these interactions for a longer period of time, they should therefore show the largest increase in velocity dispersion. Evidence in favour of such internal mechanisms has come from both observations (Yu & Liu 2018) and simulations (Saha et al 2010;Grand et al 2016;Aumer et al 2016). An alternative explanation is that in the early Universe, conditions were generally more chaotic (Wisnioski et al 2015), so that any stars born at that time were more likely to have higher velocity dispersion.…”
Section: Resolved Studies and Galaxy Formation Simulationsmentioning
confidence: 99%
“…Looking at the age-velocity dispersion relation in the solar neighbourhood (e.g. Yu & Liu 2018, Aumer & Binney 2009), we investigate the signature of an age-rotation relation in the distribution of total space velocities, as defined in Eq.8, as a function of photometric rotation period. Fig.…”
Section: The Age-velocity Dispersion Relationshipmentioning
confidence: 99%